Kemampuan Akumulasi Kromium pada Insang Ikan Nila - Siti Rizki Annafia; Devi Ulinuha; Alfi Hermawati Waskita Sari (Current Trends in Aquatic Science, 2024)
Contamination of Heavy metal has a crucial issue not only in Indonsia but also in Global where are contamination of heavy metals can cause pollution in waters which has adversely affects not only to water quality but also affects to aquatic organism life. One of the dangerous heavy metals was found in the waters is chromium (Cr). Chromium contamination in the waters can caused by industrial waste like : tanning leather, paint mixture, etc. Tilapia is an economic fish in that has ability to accumulate heavy metals. This aim of this study is to determine the ability of Cr heavy metal accumulation in gills. Experimental research was conducted on tilapia measuring 10-13 cm by giving Cr exposure at different concentrations (0 ppm, 30 ppm and 60 ppm) for 96 hours. Measurement of Cr content in gill organs was read by using an Atomic Absorption Spectrophotometer (AAS) at the integrated laboratory of the faculty of Mathematics and Natural Sciences, Udayana Univesity. The results obtained from this study indicated that there were differences in gill accumulation with Cr exposure 30 ppm and 60 ppm of Cr. The highest Cr accumulation of Cr in the gill organs with exposure by Cr 60 ppm (13,491 ppm) and 6,515 ppm at exposure to Cr 30 ppm.